Using Period Analysis to Timely Assess and Predict 5-Year Relative Survival for Liver Cancer Patients From Taizhou, Eastern China - Wang, Youqing; Zhang, Luyao; Han, Fang; Li, Runhua; Cheng, Yongran; Jiang, Xiyi; Wang, Liangyou; Chen, Jinfei; Ji, Jianguang; Zhang, Yuhua; Chen, Tianhui (Frontiers in Oncology, 2022)
Introduction: While timely assessment of long-term survival for patients with liver cancer is essential for evaluation on early detection and screening programs of liver cancer, those data are extremely scarce in China. We aimed to timely and accurately assess long-term survival for liver cancer patients in eastern China. Methods: Patients diagnosed with liver cancer during 2004-2018 from four cancer registries with high-quality data from Taizhou, eastern China were included. Period analysis was used to calculate 5-year relative survival (RS) for overall and the stratification by sex, age at diagnosis and region. The projected 5-year RS of liver cancer patients during 2019-2023 was also assessed using a model-based period analysis. Results: Overall 5-year RS for patients with liver cancer during 2014-2018 reached 32.4%, being 29.3% for men and 36.1% for women. 5-year RS declined along with aging, decreasing from 38.2% for age<45 years to 18.8% for age > 74 years, while 5-year RS for urban area was higher compared to rural area (36.8% vs 29.3%). Projected overall 5-year RS of liver cancer patients could reach 41.4% during the upcoming period 2019-2023. Conclusions: We provided , for first time in China using period analysis, most up-to-date 5-year RS for patients with liver cancer from Taizhou, eastern China and also found 5-year RS for liver cancer patients have improved greatly during 2004-2018, which has important implications for timely evaluation on early detection and screening programs for patients with liver cancer in eastern China.